Optimalisasi Produksi Benih Botani Bawang Merah (Allium ascalonicum L) Varietas Bima Brebes di Kepulauan Bangka Belitung - Kartika Kartika; Winda Wahyuni; Eka Sari (Jurnal Agroekoteknologi, 2026)
The use of botanical seeds, better known as True Shallot Seed (TSS), as a seed source for shallot production has technical and economic standards to support the development of shallots in the Bangka Belitung Islands. This research was conducted in a farmer's garden in Central Bangka Regency, with coordinates 2°13'02"S 106°09'49"E at an altitude of 50-100 meters above sea level from June to September 2024. This study aimed to determine the boron dose and BAP concentration in increasing the flowering percentage and TSS production in Bangka Belitung. This experiment used shallots bulbs of the Bima Brebes variety with an experimental design in the form of a two-factor randomized block split plot, where the first factor was the boron dose consisting of three levels, namely 0 kg ha-1 (B0), 1 kg ha-1 (B1) and 2 kg ha-1 (B3). The second factor of this study is the BAP concentration with 4 levels, namely 0 ppm (P1), 50 ppm (P2), 100 ppm (P3), and 150 ppm (P4). Each treatment was repeated five times, so that there were 60 experimental units with the number of plants in each treatment combination being 9 plants, so that the total number of plants was 540 plants. The results of the study showed an interaction between boron and BAP on the parameters of fresh tuber weight and number of seeds per bulb. Boron application at a dose of 2 kg ha-1 was able to increase the fresh weight of bulbs, the number of seeds per bulb and the number of capsules per bulb in shallot plants of the Bima Brebes variety in the lowlands of the Bangka Belitung Islands. BAP treatment did not actually affect the overall observations in this study.